2021
DOI: 10.1002/cpdd.922
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Opicapone and Its Metabolites in Healthy White and Chinese Subjects

Abstract: Opicapone (OPC) is a third-generation catechol-O-methyltransferase inhibitor developed to treat Parkinson disease and motor fluctuations. This open-label, single-center, phase 1 study aimed to evaluate the pharmacokinetics (PK) of OPC and its metabolites when administered as single and multiple doses in healthy White and Chinese subjects. The study enrolled a total of 30 White and Chinese healthy subjects, equally balanced among groups. The first dose of OPC was administered orally as a single dose of 50 mg on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Falcão et al found no obvious impact of ethnic factors on pharmacokinetics (PK) and pharmacodynamics (PD) profiles of OPC [ 20 ]. Besides, in a phase 1 study conducted by Xue et al, healthy Chinese and Caucasian subjects showed comparable PK characteristics of OPC after taking 50 mg OPC in multiple doses [ 21 ]. However, very little is known about the exposure–response and safety of OPC when given to the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Falcão et al found no obvious impact of ethnic factors on pharmacokinetics (PK) and pharmacodynamics (PD) profiles of OPC [ 20 ]. Besides, in a phase 1 study conducted by Xue et al, healthy Chinese and Caucasian subjects showed comparable PK characteristics of OPC after taking 50 mg OPC in multiple doses [ 21 ]. However, very little is known about the exposure–response and safety of OPC when given to the Chinese population.…”
Section: Introductionmentioning
confidence: 99%